Early Childhood Education Pre-Service Teachers’ Images of Teacher and Beliefs about Teaching - Jale ALDEMIR; Ozcan SEZER (İnönü Üniversitesi Eğitim Fakültesi Dergisi)
The purpose of this qualitative case study was to explore early childhood education pre-service teachers’ images of an early childhood education teacher and their beliefs about teaching. 14 pre-service teachers at a Northeastern State University in the United States of America agreed to participate in the study. A survey questionnaire, participants’ journal entries, and artifacts created by the participants were employed to collect the data. The categorization and coding of the data revealed that the participants’ memories of their past teachers, mentor teachers, and work experience with children affected their images of an early childhood teacher. Furthermore, the data showed the relations between the participants’ images of an early childhood education teacher and their beliefs about teaching. The authors made some implications for early childhood teacher education and teacher education in general.